Comparison of the setting characteristics of mineral trioxide-aggregate (MTA) with and without cotton pellet placement in vitro - Jimena, Dante Ferdinand M.
Sealing of the pathways of communication between the root canal system and the surrounding tissues is compulsory to the success of endodontic treatment. The development Mineral Trioxide Aggregate or MTA, a valuable endodontic material, was for the purpose of a repair material that does not irritate the surrounding tissues and has good sealing properties. MTA's sealing ability has been attributed to its hydrophilic nature and slight expansion when set in a moist environment. In pulp capping cases, the manufacturer recommends the placement of a wet cotton pellet over the material, and requires an additional visit for the cotton removal, before the tooth is permanently restored. This in vitro study aimed to find out if there is a significant difference in the setting characteristics of MTA under two conditions: 1) with moist cotton pellet and 2) without cotton pellet in an attempt to endorse the elimination of the additional visit. Eighty teeth were used in a series of experiments to evaluate the setting ability of MTA in terms of hardness, marginal adaptability and consistency. Using Chi Square and Fisher's Exact Tests, the computed p values were <0.000001 for both hardness and consistency tests, and >0.5 for marginal adaptability. Results showed that the presence of moist cotton pellet is associated with hardness and consistency of MTA, but not with marginal adaptability. In light of the findings, there is enough evidence to conclude that there is a significant difference in the setting guality of MTA when made to set with moist cotton pellet and when left to set without moist cotton pellet in vitro. However, guality of marginal adaptation was the same on both groups which is the primary concern of MTA.